ON THE FEEDING HABITS OF THE SEA STAR LUIDIA SENEGALENSIS (LAMARCK) IN THE STATE OF CEARÁ (BRAZIL) - LIMA VERDE, JOSÉ SANTIAGO; MATTHEWS, HENRY RAMOS (Arquivos de Ciências do Mar, 2018)
The sea sta.r Luidia senegalensis (Lamarck) is one of the most common asteroids of the brazilian northeast. It has a very broad geographical distribution, occuring in both sides of the Atlantic Ocean (Bernasconi, 1943).